Pengaruh Kelompok Referensi dan Kepercayaan Terhadap Keputusan Pembelian Pada Cumi Store Tanjungpinang - Maryati Maryati; Betty Leindarita (LPPM Universitas Putera Batam, 2020)
The purpose of this research was to analyze the influence of reference groups and beliefs on purchasing decisions at Cumi Store Tanjungpinang. This research used quantitative descriptive research. The technique of collecting data using a questionnaire. The population in this study were buyers who had shopped at Cumi Store Tanjungpinang. The sampling method using the Slovin formula, then taken as many as 91 respondents The t test results on the reference group variable (X1) on the purchasing decision variable (Y) produce t count of (2.114)> t table (1.663) and have a significance of 0.037 less than 0.05. The t test results on the trust variable (X2) on the purchasing decision variable (Y) produce t count of (2.608)> t table (1.663) and have a significance of 0.045 less than 0.05. Meanwhile, the results showed Y = 2.656 + 0.194 X1 + 0.137 X2 + e. The conclusion obtained based on testing shows that the reference group variable and the trust variable partially and simultaneously have a positive and significant effect on purchasing decisions at Cumi Store Tanjungpinang. With the Adjusted R Square contribution of 75.6%, the decision is influenced by the reference and belief group variables, while the remaining 24.4% is influenced by other factors that are not included in this study.